Blended Online Learning Design: Shaken not Stirred - Vaughan, Norm; Power, Michael (International Review of Research in Open and Distributed Learning, 2010)
Given the crucial role played by universities in a knowledge-based society, understanding how and under what conditions online learning (OL) can improve access to graduate studies is of the highest importance to today’s growing global economy. Over the past decade, phenomenal advances have been made in the application of communication and information technologies to support student learning in higher education. Yet, in proportion to overall provision of higher education, the use of technology by faculty for graduate-level, online learning (OL) has been minimal, especially among regular faculty. In this session, Norm Vaughan and Michael Power present an adapted form of OL, especially designed for traditional universities, with initial data from studies underway in two Canadian universities. Finally, an emerging network of researchers interested in the role of online learning within mainstream higher education is presented.